Novel method for the protection of amino alcohols and carbonyl compounds over a heterogeneous, reusable catalyst - Srivastava, P.; Srivastava, R. (Catalysis Communications, 2008)
A novel application of Al-SBA-15 catalyst in the protection of amino alcohols and carbonyl compounds is reported. N-t-butoxy carbonyl [N(Boc)] amino alcohols were protected using 2,2-dimethoxyproparic (DMP) to form acetonides. Acetonide deprotection was also studied using the same catalyst to obtain the parent amino alcohol. Protection of carbonyl compounds was Studied using neopentyl glycol, ethylene glycol and propylene glycol as the protecting agents. A series of commercially important molecules Such as 2-substituted and 2,2-disubstituted 1,3-benzodioxoles were synthesized by reacting carbonyl compounds with catechol. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Acetalization; acetonide; Amino alcohol; benzodioxole; protection

Acetalization of glycerol using mesoporous MoO3/SiO2 solid acid catalyst - Shubhangi B. Umbarkar; Kotbagi, Trupti V.; Biradar, Ankush V.; Pasricha, Renu; Chanale, Jyoti; Dongare, Mohan K.; Mamede, Anne-Sophie; Lancelot, Christine; Payen, Edmond (Journal of Molecular Catalysis A-Chemical, 2009)
Acetalization of glycerol with various aldehydes has been carried out using mesoporous MoO3/SiO2 as a solid acid catalyst. A series of MoO3/SiO2 catalysts with varying MoO3 loadings(1-20 mol%) were prepared by sol-gel technique using ethyl silicate-40 and ammonium heptamolybdate as silica and molybdenum source respectively. The sol-gel derived samples were calcined at 500 degrees C and characterized using various physicochemical characterization techniques. The XRD of the calcined samples showed the formation of amorphous phase up to 10 mol% MoO3 loading and at higher loading of crystalline alpha-MoO3 on amorphous silica support. TEM analyses of the materials showed the uniform distribution of MoO3 nanoparticles on amorphous silica support. Raman spectroscopy showed the formation of silicomolybdic acid at low Mo loading and a mixture of alpha-MoO3 and polymolybdate species at high Mo loadings. Moreover the Raman spectra of intermediate loading samples also suggest the presence of beta-MoO3. Acetalization of glycerol with benzaldehyde was carried out using series of MoO3/SiO2 catalysts with varying MoO3 loadings (1-20 mol%). Among the series, MoO3/SiO2 With 20 mol% MoO3 loadings was found to be the most active catalyst in acetalization under mild conditions. Maximum conversion of benzaldehyde (72%) was obtained in 8 h at 100 degrees C with 60% selectivity for the six-membered acetal using 20% MoO3/SiO2. Interestingly with substituted benzaldehydes under same reaction conditions the conversion of aldehydes decreased with increase in selectivity for six-membered acetals. These results indicate the potential of this catalyst for the acetalization of glycerol for an environmentally benign process. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Acetalization; Aldehyde; Glycerol; Silicomolybdic acid; solid acid

Facet dependence for solvent-modulated proton-coupled electron transfer in furfural acetalization on Pd nanostructures - Porwal, Govind; Dandekar, Pallavi; Gorai, Twinkle; Khan, Tuhin Suvra; Haider, M. Ali; Gupta, Shelaka; Vinod, C. P. (Chemical Engineering Journal, 2025)
Furfural dialkyl acetals prepared via acetalization reaction of furfural and alcohols are promising biofuels. Using defined experiments and density functional theory (DFT) simulations, the structure-dependent activity and selectivity for furfural acetalization reaction in the presence of alcohols (methanol, ethanol, propanol and butanol) as solvents was studied over well-defined supported Pd nanostructures (octahedra (111), cubes (100) and spheres (both (111) and (100)). Pd cubes supported over TiO2 in the presence of ethanol as a solvent (at 303 K and balloon pressure H-2) exhibited 78 % conversion and 100 % selectivity for furfural diethyl acetal product in a short time (similar to 180 min). In contrast, Pd octahedra (111) and Pd spheres showed low conversions (18 % and 6 %) at the same reaction conditions. Interestingly, when used as a solvent, methanol showed the highest conversion (90 %) and selectivity (100 %) for furfural acetalization over Pd cubes. DFT simulations provided mechanistic insight into the reactivity of the two different Pd facets (111) and (100) in the presence of alcohol molecules towards furfural acetalization reaction. A three-step reaction mechanism was proposed for furfural acetalization with alcohols: (i) alcohol hydroxyl-dehydrogenation (ii) hydrogenation of furfural carbonyl oxygen, and (iii) formation of hemiacetal product. For all three steps, Pd (100) exhibited low activation barriers (51.6, 26.7 and 76.2 kJ/mol) compared to Pd (111) surface (78.6, 35.8 and 92.2 kJ/mol) in the presence of ethanol. The activation barriers for the above steps were further reduced to 47.8, 23.9 and 64.6 kJ/mol on Pd (100) in the presence of methanol, explaining the experimental high reactivity aided by methanol. DFT calculations elucidated the role of the hydrogen bonding network between the solvent molecules and adsorbate, enabling proton-coupled electron transfer for accelerated reactions.
Keywords: Acetalization; DFT; facet-dependent reactivity; furfural; Furfural dialkyl acetals; solvent effect